HSF2 drives breast cancer progression by acting as a stage-specific switch between proliferation and invasion - Pessa, Jenny C.; Paavolainen, Oona; Hästbacka, Hendrik S. E.; Puustinen, Mikael C.; Da Silva, Alejandro J.; Pihlström, Sandra; Gramolelli, Silvia; Boström, Pia; Hartiala, Pauliina; Peuhu, Emilia; Joutsen, Jenny; Sistonen, Lea (American Association for the Advancement of Science (AAAS), 2026)
Breast cancer is hallmarked by phenotypic transitions enabling abnormal cell proliferation and invasion. The stress-protective transcription factor heat shock factor 2 (HSF2) is associated with cancer, but its function in breast carcinogenesis remains poorly understood. Analysis of human breast tumor samples and mouse in vivo xenografts uncovered that HSF2 expression and activity undergo dynamic changes as a function of tumor progression. HSF2 expression, nuclear localization, and coexpression with the proliferation marker Ki67 are increased in ductal carcinoma in situ (DCIS), suggesting that HSF2 designates hyperplastic cells underlying tumor expansion. In mouse xenografts, HSF2 localization switches from nuclear to cytoplasmic upon DCIS-to-invasive transition. Using cell-based models, we identify canonical transforming growth factor–β (TGF-β) signaling as the molecular mechanism regulating HSF2. TGF-β–mediated down-regulation of HSF2 allowed acquisition of an invasive cell phenotype, which was counteracted by ectopic HSF2. Together, we propose that HSF2 acts as a stage-specific switch between proliferation and invasion in breast cancer.